2021
DOI: 10.1007/s00405-020-06560-0
|View full text |Cite
|
Sign up to set email alerts
|

Is taste and smell impairment irreversible in COVID-19 patients?

Abstract: Objective It is known that the COVID-19 disease, which has affected the whole world, causes symptoms, such as cough, fever, shortness of breath, muscle pain, fatigue, diarrhea, headache and sore throat, in addition to various clinical findings, such as loss of smell and taste. In this study, we aimed to reveal the loss of sense of taste and smell in COVID-19 patients and to investigate whether these sensory losses are permanent in the healing process of the disease. Method This prospective study included 94 CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…The remaining 18 studies were conducted in other regions (a pie chart showing distribution is included in the supplementary data provided— S1 Fig ). 10 studies were conducted in Asia: Turkey (n = 5) [ 18 , 27 , 38 , 41 , 50 ], Iran (n = 2) [ 22 , 55 ], India (n = 2) [ 33 , 52 ], Israel (n = 1) [ 32 ]. Four studies were conducted in North America: United States (n = 4), [ 21 , 42 , 48 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The remaining 18 studies were conducted in other regions (a pie chart showing distribution is included in the supplementary data provided— S1 Fig ). 10 studies were conducted in Asia: Turkey (n = 5) [ 18 , 27 , 38 , 41 , 50 ], Iran (n = 2) [ 22 , 55 ], India (n = 2) [ 33 , 52 ], Israel (n = 1) [ 32 ]. Four studies were conducted in North America: United States (n = 4), [ 21 , 42 , 48 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies were conducted in Africa: Egypt (n = 2) [ 34 , 49 ], and two in South America: Brazil (n = 1) [ 53 ], Chile (n = 1) [ 15 , 53 ]. Of the 44 studies, twenty-five (56.8%) reported no funding requirements for the project [ 16 , 18 , 19 , 22 , 27 30 , 32 , 33 , 39 , 40 , 42 47 , 49 51 , 53 , 58 ]; six (13.6%) studies reported funding for the project (sources included academic institutions, government and not-for-profit organizations) [ 15 , 24 , 25 , 31 , 48 , 57 ], and thirteen (29.5%) did not report whether funding was provided [ 17 , 21 , 23 , 26 , 37 , 38 , 52 , 54 56 , 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, Amer and colleagues noted that females had better recovery at 1 month from COVID-19 onset (83.9% vs. 62.5%, p < 0.005), proposing elevated androgens in males that enhance transcription of TMPRSS2 [ 56 ]. However, other studies have found no association between sex and OD/GD, making the association unclear [ 57 59 ]. Increased age (> 55 years) has also been associated with longer duration of GD (21.6 vs. 33.61 days, p = 0.019) [ 60 ], whereas ages > 60 years have been correlated with longer durations of OD ( p < 0.001) [ 61 ].…”
Section: Main Textmentioning
confidence: 99%